BALANCED SCORECARD AS AN INSTRUMENT FOR MEASURING ORGANIZATIONAL PERFORMANCE BASED ON A BALANCE OF FINANCIAL, CUSTOMER, INTERNAL PROCESS, AND LEARNING PERSPECTIVES - Didit Darmawan; Muhammad Fanani; Ahmat Basori; Muhammad Syabani; Ahmad Zakiyuddin Al-Karimi (Universitas Negeri Makassar, 2026)
Abstract: This study examines how balanced scorecard serves as an organizational performance measurement tool by integrating financial, customer, internal process, and learning perspectives into a coherent framework. Drawing upon systematic literature examination, the research explores causal relationships linking learning investments to internal process excellence, customer satisfaction, and financial outcomes. Strategic maps visualize these causal chains and communicate strategic logic throughout organizations. Design processes translate vision into specific objectives, metrics, targets, and initiatives across four perspectives. Balance between outcome and driver indicators, financial and nonfinancial measures, and short-term and long-term focus ensures comprehensive performance visibility. Cascade mechanisms align unit and individual objectives with organizational scorecard, creating vertical coherence. Integration with planning, budgeting, and review processes ensures measurement systems influence resource allocation and decisions. Validation through data correlation tests causal hypotheses underlying strategic maps. Technology facilitates data collection automation and performance visualization. Periodic revision maintains alignment between measurement systems and evolving priorities. Organizational learning from performance data enables continuous improvement. Leadership commitment, strategic clarity, and transparency culture constitute implementation foundations. Future research may explore industry-specific adaptations and digital technology applications.Keywords: Balanced Scorecard, Performance Measurement, Financial Perspective, Customer Perspective, internal Processes, Learning and Growth, Causal Relationships